From Expression to Connection: Decoding Sana All’s Linguistic Meanings in Communication Context - Dangalao, Tong Kabenbelan (Future Science / FSH-PH Publications, 2024)
very age group and generation uses different lingo, jargon, and forms of communication in casual conversations. These lingos could be introduced by the fashions, significant events, radio shows, movies, TV shows, songs, and literature of their time, among many other devices. Additionally, technology has changed some words, adding new ones that are more inventive and simpler to type. The study aimed to analyze the linguistic meaning of